Direct ink writing of boron carbide monoliths. Issue 16 (December 2021) - Lakhdar, Yazid; Tuck, Christopher; Terry, Anna; Spadaccini, Christopher; Goodridge, Ruth
Highlights: Paste formulation and printing parameters were linked for the first time to the surface and bulk defects influencing the surface quality, hardness and microstructure of B4 C monoliths made by DIW. The rheological properties of B4C pastes were linked to their printing behaviour using several extrusion orifice diameters as well as various printing strategies and substrate properties. A 406 μm extrusion orifice diameter resulted in significant improvements of the surface quality, shape retention and density compared with the 584 μm orifice. A detailed inspection of the external and internal characteristics of dense B4C samples using SEM imaging and μCT scanning revealed that crack-free multi-layer monoliths with a fully dense microstructure could be fabricated, but a 3D array of inter-strut mesopores could not be avoided without sacrificing shape retention. Abstract: Direct ink writing – an extrusion-based additive manufacturing process – followed by pressureless sintering was investigated to produce boron carbide monoliths. The effects of ceramic powder loading and Pluronic binder concentration on the rheology of boron carbide pastes were studied and linked to both processing behaviour and final outcome in terms of sintered density and hardness. The effects of printing parameters, in particular orifice diameter and printing speed, were also investigated. Reducing the size of the extrusion nozzle from 584 μm to 406 μm led to significantly better shape retention, lower surface roughness, as well as higher density and hardness. A 203 μm printing orifice was also trialled but was unsuccessful due to faster drying kinetics that occurred with smaller ceramic struts resulting in rapid warping and nozzle clogging. Carbon-black – 8 wt% relative to B4 C – acted as an effective sintering aid to increase both density and hardness. After optimisation of feedstock and printing parameters, few-layer samples (3–5 layers) had a density as high as ∼ 97 % TD and a hardness of ∼ 30 GPa. On the other hand, 18-layer specimens had a sintered density of ∼ 87 % TD, despite a fully dense microstructure, due to the formation of a 3D array of inter-strut pores. Nevertheless, several issues that arose during manufacturing and post-processing were detrimental to the density and structural integrity of printed specimens; these issues were identified, discussed, and suggestions for future work are provided.